Band electron spectrum and optical properties of KDP-crystals under the external hydrostatic pressure - Stetsiv, R.Ya. (Condensed Matter Physics, 1999)
The electron spectrum of the KDP-type crystals has been investigated as a
function of the external hydrostatic pressure using the tight-binding approximation.
The joint density of electron states, real and imaginary parts of the
dielectric permeability, refraction indices, the gyration coefficient, absorption
and reflection coefficients for different polarizations of light are determined.
Their pressure and frequency dependencies are investigated. The
results are discussed by comparing them with the experimental data on
piezooptic coefficients. The anomalous behaviour of the optical constants
at the pressure p ~≃ 17 kbar is due to the transformation of the hydrogen
bond potential from a double minimum one to a single minimum one, where
the proton is localised at the midpoint of the hydrogen bond. В наближенні сильно зв’язаних електронів досліджено залежність
зонного електронного спектру кристалів типу KDP від зовнішнього
гідростатичного тиску. Розраховані комбінована густина електронних станів, дійсна та уявна частини діелектричної проникності для
різної поляризації світла, показники заломлення, коефіцієнт гірації,
коефіцієнти поглинання та відбивання світла. Досліджена їх залежність від енергії світлової хвилі та від зовнішнього гідростатичного
тиску. Результати порівнюються з експериментальними даними для
п’єзооптичних коефіцієнтів. Отримані аномалії оптичних констант
при тиску p ~≃ 17 кбар зумовлені трансформацією потенціалу протона на зв’язку з двомінімумного в одномінімумний.